1999
DOI: 10.1021/np980536m
|View full text |Cite
|
Sign up to set email alerts
|

Flavones and Sesquiterpene Lactones from Achillea atrata subsp. multifida:  Antimicrobial Activity

Abstract: Four flavones (1-4) and nine sesquiterpene lactones (5-13), one of them (5) a new compound, were isolated from the aerial parts of Achillea atrata L. subsp. multifida. Although the crude extract demonstrated in vitro inhibitory activity against Candida albicans and Bacillus subtilis, all isolated flavones were active against B. subtilis. Flavones 1, 2, and 3 were also active against C. albicans, while 1 and 3 exhibited activity against E. coli, as well. None of the tested lactones (7, 9, 12, and 13) showed any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…Two flavonoid aglycones: 1) 5,7,3′-Trihydroxy-6,8,4′-trimethoxy flavone (acerosin), or 5,7,8-trihydroxy-6,3′,4′-trimethoxy flavone, and 2) 5,8-dihydroxy-6,7,4′-trimethoxy flavone (pedunculin) (Ristic et al, 2004) A. atrata subsp. multifida Flavones and sesquiterpene lactones (Aljančić et al, 1999) A. biebersteinii Afan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two flavonoid aglycones: 1) 5,7,3′-Trihydroxy-6,8,4′-trimethoxy flavone (acerosin), or 5,7,8-trihydroxy-6,3′,4′-trimethoxy flavone, and 2) 5,8-dihydroxy-6,7,4′-trimethoxy flavone (pedunculin) (Ristic et al, 2004) A. atrata subsp. multifida Flavones and sesquiterpene lactones (Aljančić et al, 1999) A. biebersteinii Afan.…”
Section: Resultsmentioning
confidence: 99%
“…Many Achillea species are rich sources of flavones (Falk et al, 1975;Aljančić et al, 1999;Moradkhani et al, 2014), other flavonoids (Bruno and Herz, 1988;Tzakou et al, 1995a; …”
Section: Introductionmentioning
confidence: 99%
“…They are found in many plants derived from several different plant species have significant antimicrobial activity in vitro [28]. The observed activity of plants studied here in might be due to the presence of sesquiterpene lactones and flavonoids, because some plant extracts showed that a high level of antimicrobial activity and also possibly due to synergistic interactions between the components of these extracts [27]. A. millefolium was found to be mildly active against E. coli, P. aeruginosa, S. aureus, Salmonella enteridis, Aspergillus niger, and C. albicans [29] In another study, the methanol extract and its water insoluble part of A. biebersteinii were evaluated for their antimicrobial activities in vitro [30] and found to be active on B. cereus, C. perfringens, and C. albicans.…”
Section: Resultsmentioning
confidence: 68%
“…The plant used in this study may contain this subtance. Flavonoids (or bioflavonoids -from Latin flavus -yellow, their colour in nature) are a class of plant secondary metabolites were demonstrated to possess antimicrobial properties and several investigations have examined the relationship between flavonoid structure and antibacterial activity [27]. Promising evidence has clearly shown that sesquiterpene lactones are a class of chemical compounds; they are sesquiterpenoids (built of three isoprene units) containing a lactone ring.…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpenes were shown to possess antimicrobial activity against Gram positive bacteria such as Bacillus subtilis, Escherichia coli and S. aureus (Aljancic et al, 1999;Anke & Sterner, 1991;Fortuna et al, 2011;Lin et al, 2003). Additionally, sesquiterpenes lactones were reported to posses anti H. pylori activity (Konstantinopoulou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%